Creating a Tourist Destination Route Database as a Tourism Information Service in West Sumbawa Regency - Fahri Hamdani; Yuliadi Yuliadi; Halid Nuryadi; Siska Atmawan Oktavia; Herliana Rosika; Fadhli Dzil Ikram (Brilliance: Research of Artificial Intelligence, 2025)
West Sumbawa Regency is one of the regencies on Sumbawa Island, West Nusa Tenggara Province. Tourism is a popular activity; most people use it to fill their free time amid their busy lives. Tourism is vital in driving national economic growth because it is one of the development sectors that can spur economic growth in a region. The impact of current technological advances has resulted in all types of information being presented online. The West Sumbawa Regency Government has problems and difficulties conveying information about existing tourism because there are no information media that the public can easily access. Currently, West Sumbawa Regency does not have a tourist route search application that tourists use as an alternative to finding travel routes by tourists. Based on these conditions, media is needed to find tourist routes and a medium for promoting tourism and its products to tourists. It can make it easier for tourists to find the shortest route to a more efficient tourist spot. In addition, local government and tourism industry entrepreneurs are used as media to promote tourist attractions and their products and tourist needs. A tourist route database was developed using the waterfall method, PHP programming, and the MySQL database as a database management system (DBMS). The results are a tourist destination route database and a website-based tourism information service expected to make it easier for the public to obtain information about tourist routes in West Sumbawa Regency.